2023
DOI: 10.3390/su15042856
|View full text |Cite
|
Sign up to set email alerts
|

Reuse of Pretreated Red Mud and Phosphogypsum as Supplementary Cementitious Material

Abstract: The combination of red mud (RM) and phosphogypsum (PG) can exert the alkalinity of RM and the acidity of PG as a calcium source to promote the gel hardening of composite cementitious material, which effectively improves the reutilization efficiency of RM and. In this study, the effects of the ratio and content of pretreated RM and PG on the non-evaporated water, porosity, hydration products, mechanical properties, pore size distribution, and microstructure of composite cementitious materials were investigated.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 62 publications
0
2
0
Order By: Relevance
“…In addition, because its chemical composition is similar to that of natural gypsum, PG can replace some natural gypsum to produce cement retarder [ 17 ]. In recent years, scholars have found that PG contains a great deal of minerals such as SO 3 , CaO, SiO 2 , etc., which are similar to the chemical composition of cement and can replace part of cement as a cementitious material [ 18 ]. It is important to improve the working performance of PG-based cementitious materials, which can be compounded by a certain amount of admixtures, such as granulated blast-furnace slag [ 19 ], fly ash [ 20 ], silica fume [ 21 ], steel slag [ 22 ], and other common admixtures, to achieve a comprehensive use of PG.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, because its chemical composition is similar to that of natural gypsum, PG can replace some natural gypsum to produce cement retarder [ 17 ]. In recent years, scholars have found that PG contains a great deal of minerals such as SO 3 , CaO, SiO 2 , etc., which are similar to the chemical composition of cement and can replace part of cement as a cementitious material [ 18 ]. It is important to improve the working performance of PG-based cementitious materials, which can be compounded by a certain amount of admixtures, such as granulated blast-furnace slag [ 19 ], fly ash [ 20 ], silica fume [ 21 ], steel slag [ 22 ], and other common admixtures, to achieve a comprehensive use of PG.…”
Section: Introductionmentioning
confidence: 99%
“…Few studies have examined the technology of the use and recovery of lithium slag. Exploring uses of lithium slag is beneficial to the sustainable development of lithium salt industry, saves natural resources, and protects the environment (Li et al, 2021;Dong et al, 2023).…”
Section: Introductionmentioning
confidence: 99%